Bahasa Inggris - Nila Lusiana; Erfan AR Lainjong; Arpin (Journal of Health, Technology and Science (JHTS), 2022)
Gout arthritis is a progressive disease due to the deposition of monosodium urate (MSU) crystals in joints, kidneys, and other connective tissues as a result of chronic hyperuricemia. The purpose of this study was to compare uric acid levels in men and women aged 45-60 years.The type of research used in this research is observational analytic with a quantitative approach and the method used in this research is Enzymatic Colorimetric (Uricase). This method uses the aid of a spectrophotometer to measure uric acid levels. The spectrophotometer used in this research is Pentra C200.The results of the research conducted at the UPTD Balai LABKESDA Gorontalo Province showed that abnormal uric acid levels were more in men than uric acid levels in women where the abnormal number in men was 7 respondents and in women only 4 respondents. This is because men have a higher risk of developing gout compared to women whose risk will be the same as men when entering the age or period of menopause.